BMP delivery complements the guiding effect of scaffold architecture without altering bone microstructure in critical-sized long bone defects: A multiscale analysis. (1st September 2015) - Cipitria, A.; Wagermaier, W.; Zaslansky, P.; Schell, H.; Reichert, J.C.; Fratzl, P.; Hutmacher, D.W.; Duda, G.N.
Graphical abstract: Abstract: Scaffold architecture guides bone formation. However, in critical-sized long bone defects additional BMP-mediated osteogenic stimulation is needed to form clinically relevant volumes of new bone. The hierarchical structure of bone determines its mechanical properties. Yet, the micro- and nanostructure of BMP-mediated fast-forming bone has not been compared with slower regenerating bone without BMP. We investigated the combined effects of scaffold architecture (physical cue) and BMP stimulation (biological cue) on bone regeneration. It was hypothesized that a structured scaffold directs tissue organization through structural guidance and load transfer, while BMP stimulation accelerates bone formation without altering the microstructure at different length scales. BMP-loaded medical grade polycaprolactone–tricalcium phosphate scaffolds were implanted in 30 mm tibial defects in sheep. BMP-mediated bone formation after 3 and 12 months was compared with slower bone formation with a scaffold alone after 12 months. A multiscale analysis based on microcomputed tomography, histology, polarized light microscopy, backscattered electron microscopy, small angle X-ray scattering and nanoindentation was used to characterize bone volume, collagen fiber orientation, mineral particle thickness and orientation, and local mechanical properties. Despite different observed kinetics in bone formation, similar structural properties on a microscopic and sub-micron level seem to emerge in both BMP-treated and scaffold only groups. The guiding effect of the scaffold architecture is illustrated through structural differences in bone across different regions. In the vicinity of the scaffold increased tissue organization is observed at 3 months. Loading along the long bone axis transferred through the scaffold defines bone micro- and nanostructure after 12 months.